Explicit versus implicit evaluation to detect inappropriate medication use in geriatric outpatients. (2nd July 2020) - Bahat, Gulistan; Ilhan, Birkan; Bay, Ilker; Kilic, Cihan; Kucukdagli, Pinar; Oren, Meryem Merve; Karan, Mehmet Akif
Abstract: Aim: The rates and reasons why clinicians decide not to follow recommendations from explicit-criteria have been studied scarce. We aimed to compare STOPP version 2 representing one of the most commonly used excplicit tool with the implicit comprehensive geriatric assessment mediated clinical evaluation considered as gold standard. Methods: Two hundred and six ( n = 206) outpatients ≥65 years old were included. The study was designed as retrospective, cross-sectional, and randomised. STOPP version 2 criteria were systematically used to assess pre-admission treatments followed by implicit clinical evaluation regarding two questions: Were the STOPP criteria recommendations valid for the individual patient and were there any potentially inappropriate-prescription other than depicted by STOPP version 2 criteria? The underlying reason(s) and associated clinical-features were noted. Results: About 62.6% potentially inappropriate-prescriptions were identified (0.6 per-subject) according to systematic application of STOPP v2 while it was 53.4% (0.5 potentially inappropriate-prescriptions per subject) by clinician's application of STOPP v2. Prevalence of non-compliance was 14.7% in 18 (21.7%) of 83 patients identified by systematic application. Suggestion to stop a drug was not accepted because of need of treatment despite likelihood of anticipated side-effects in about 2/3 and with no-anticipated side-effects in about 1/3 of non-compliances. Not following STOPP v2 was significantly associated with lower functional level. According to clinician's implicit-evaluation, there were an extra 59.2% potentially inappropriate-prescriptions (0.6 per subject) in 80 (38.8%) patients yielding a total of 112.6% potentially inappropriate-prescription. Conclusions: Most of the STOPP v2 directed drug cessations are decided valid by the clinicians. In patients with higher functional dependency, it is likely that they are not followed due to palliation focussed care/patient–family preferences. There may be as much as STOPP v2 identified potentially inappropriate-prescriptions by implicit evaluation in a significant percent of geriatric patients signifying need for comprehensive geriatric evaluation in practice.